PROBLEMS OF TECHNOGENIC CHANGES OF GEOLOGICAL ENVIRONMENT ON THE TERRITORIES OF KYIV - KOSTIUCHENKO, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The problems of technogenic changes of geological environment of the territory of Kyiv are represented. Thedescription of basic factors of development of unfavorable engineering-geological processes is given. The results of studying of changes of engineering-geological conditions on the areas of historical sights and new buildings are analyzed. The measures for the maintainance of equilibrium of geological environment are proposed.